THE EVALUATION OF NATIONAL ECONOMIC RECOVERY PROGRAM (PEN) CLUSTER OF MICRO, SMALL AND MEDIUM ENTERPRISE - Johnson Kennedy, Posma Sariguna (Universitas Kristen Indonesia, 2021)
MSMEs spread throughout Indonesia are expected to be one of the main drivers in the national economic recovery (PEN) due to the COVID-19 pandemic. This study aims to evaluate the programs that have been carried out and the budget used in the PEN Program specifically for Micro, Small, and Medium Enterprises (MSMEs) in 2020 and look at the program in 2021. The research method used is a qualitative method by reviewing the literature related to research objectives. The PEN scheme for MSMEs is in the form of a debt restructuring program, postponement of debt installation payments for six months; Subsidizing installation interest of 6% and tax subsidy of 0%; MSME actors can also apply for loans with low-interest rates of only 3%; and productive presidential assistance for MSMEs (BPUM) that have not been in contact with banks, amounting to Rp. 2.4 million, which is allocated to 12 million business actors. In general, some MSMEs stated that their business was able to survive after obtaining BPUM funds. Keywords: National Economic Recovery, Micro, Small and Medium Enterprises (MSMEs), COVID-19 Pandemic